Salivary IgG levels in neonatal calves and its association to serum IgG: an observational pilot study - Johnsen, Julie Føske (Transl Anim Sci, 2019)
The diagnosis of inadequate transfer of colostrum immunoglobulin G (IgG) to calf serum, often known as failure of passive transfer (<10 g/L IgG1 at 24 to 48 h), necessitates blood sampling from the calf and in some instances the presence of a veterinarian. Sampling saliva is both less invasive and easy for the producer. Previous research has shown that quantification of saliva IgG is possible in juvenile and adult cattle. The objectives of this observational pilot study were to investigate whether IgG can be quantified in neonatal calf saliva, if it is correlated to serum IgG concentrations, and if the indirect quantification of saliva IgG is achievable by use of a digital refractometer. Paired blood and saliva samples were collected from 20 healthy dairy calves aged 1 to 3 d. In these samples, IgG was quantified directly with single radial immunodiffusion and indirectly by use of a digital refractometer indicating Brix % (a subsample of n = 12 saliva samples). A strong positive correlation (r = 0.7, P < 0.001) between saliva IgG (mean ± SD; 0.2 ± 0.11 g/L) and serum IgG (32.1 ± 11.94 g/L) was found. Saliva IgG ranged from the lowest detectable value, 0.1 g/L (n = 6 samples) to 0.6 g/L. Saliva Brix (1.2 ± 0.69%) was not significantly correlated to serum IgG (n = 12, r = 0.43, P = 0.155); however, it was significantly correlated to saliva IgG (n = 12, r = 0.7, P = 0.018) and Brix in serum (n = 12, r = 0.7, P = 0.013). We conclude that IgG was quantifiable in most of the saliva samples. For saliva IgG to be of any value with regards to detecting failure of passive transfer, future studies should investigate methods that can detect IgG <0.1 g/L. The results indicate that saliva IgG can be used to predict serum IgG at levels above 10 g/L, which may warrant further exploration of the use of saliva in the surveillance of failure of passive transfer. The results of the current pilot study did not support the potential usage of a Brix % refractometer to quantify saliva IgG.